Maternal iron deficiency anaemia in pregnancy: Lessons from a national audit. (3rd August 2022) - Churchill, David; Ali, Hind; Moussa, Mahmoud; Donohue, Ciara; Pavord, Sue; Robinson, Susan E.; Cheshire, Katherine; Wilson, Paul; Grant‐Casey, John; Stanworth, Simon J.
Summary: We describe the management and the prevalence of iron deficiency anaemia (IDA) during pregnancy by comparison to standards. A cross‐sectional national cohort study of women who had given birth six weeks prior to data collection was conducted at maternity units in the UK and Ireland. Participating centres collected data from 10 consecutive pregnant women. Analysis was descriptive to define the prevalence of IDA in pregnancy and the puerperium, and to compare the outcomes in women who had IDA with women who did not have anaemia anytime during pregnancy. Eighty‐six maternity units contributed data on 860 pregnancies and births. The overall prevalence of IDA during pregnancy was 30.4% and in the puerperium 20%. Anaemic women were more likely to be from ethnic minorities, odds ratio 2.23 (1.50, 3.32). Adherence to national guidance was suboptimal, and the prevalence of anaemia in pregnancy remains very high. There is pressing need to explore barriers to early identification and effective management of iron deficiency. IDA should be considered a major public health problem in the UK.